Single layer drying behaviour of potato slices in a convective cyclone dryer and mathematical modeling - Akpinar, E; Midilli, A; Bicer, Y (Pergamon-Elsevier Science Ltd, 2003)
The main objective pursued in this paper is to investigate the single layer drying behaviour of potato slices experimentally in a convective cyclone dryer and also to perform mathematical modeling by using single layer drying models in the literature. Drying experiments of potato slices with the thicknesses of 12.5 and 8 mm were conducted at inlet temperatures of drying air of 60, 70 and 80 degreesC and with drying air velocities of 1 and 1.5 m/s. It was concluded that potato slices with thickness of 12.5 mm would dry perfectly in the range of 460-740 min, while those with thickness of 8 mm would dry in the range of 280-520 min in these drying conditions in the convective type cyclone dryer. Additionally, the mathematical model describing the single layer drying curves was determined by non-linear regression analysis, and an approximation of the diffusion model was selected as the most suitable model to describe the drying curve equation of potato slices. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: drying; single layer; dryer; potato; mathematical modeling; diffusion